2005
DOI: 10.1063/1.2061872
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric oscillation of adherent targeted ultrasound contrast agents

Abstract: With a lipid shell containing biotin, micron-sized bubbles bound to avidin on a porous and flexible cellulose boundary were insonified by ultrasound. The oscillation of these targeted microbubbles was observed by high-speed photography and compared to the oscillation of free-floating microbubbles. Adherent microbubbles were observed to oscillate asymmetrically in the plane normal to the boundary, and nearly symmetrically in the plane parallel to the boundary, with a significantly smaller maximum expansion in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 27 publications
4
65
0
5
Order By: Relevance
“…Finally, asymmetric oscillations may arise in the vicinity of the wall. The eccentricity of bubbles in the vicinity of a capillary wall and driven at comparable pressures has been indeed reported to be close to 0.7 [95], although these observations were made on adherent bubbles. In our experiments, the possible adhesion to the wall was excluded by verifying with the optical tweezers whether bubbles were indeed non-adherent, yet in contact with the wall.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, asymmetric oscillations may arise in the vicinity of the wall. The eccentricity of bubbles in the vicinity of a capillary wall and driven at comparable pressures has been indeed reported to be close to 0.7 [95], although these observations were made on adherent bubbles. In our experiments, the possible adhesion to the wall was excluded by verifying with the optical tweezers whether bubbles were indeed non-adherent, yet in contact with the wall.…”
Section: Resultsmentioning
confidence: 68%
“…the non-invasive detection of a specific disease at a molecular level, it will be crucial to develop methods for selectively detecting adherent UCA microbubbles that have bound to specific molecular targets from freely flowing ones, primarily based on a change in their acoustic response. Considerable differences in the amplitude of oscillations [95,96] and in the spectral response [97] were reported recently. In general, the studies on UCA microbubble dynamics suffer from the lack of control on bubble position, however, and they are therefore based on ensemble averaging and statistical observations of many different bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…16 Third, Zhao et al observed previously that microbubbles adherent to a vessel wall oscillate asymmetrically in the plane normal to the boundary, in contrast to free microbubbles which oscillate symmetrically. 5 Further, for a low transmission pressure, the volume oscillation was observed to decrease in comparison with free agents. Asymmetrical oscillation of a cavitation bubble and formation of a jet near a boundary or within a vessel have been studied both theoretically and experimentally by number of research groups.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, tethers on the order of nanometers in length connect these small bubbles to endothelial cells and bring them in close contact with a boundary. The oscillation of these adherent microbubbles was observed to be asymmetrical by high-speed photography 5 but their acoustic response has not been reported previously. Optimal detection of bound agents would require differentiating their echoes from those produced by freely circulating agents and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 92%
“…2(d)]. Similar experimental parameters were used in works published by Garbin et al, 13 Zhao et al, 14 and Vos et al 15 In the adherent microbubble model, the vessel wall was simulated using the mechanical properties of a stiff arterial wall 8 with the stiffness of ͑E = 1 MPa͒ and the density of 1000 kg/ m 3 . The arterial wall was assumed to be incompressible.…”
Section: Resultsmentioning
confidence: 99%